The efficacy of single posterior debridement, bone grafting and instrumentation for the treatment of thoracic spinal tuberculosis - Zhi Yi (Nature Portfolio, 2021)
Abstract The aim of this study was to investigate the clinical efficacy of single posterior debridement, bone grafting and instrumentation for the treatment of thoracic spinal tuberculosis in adult patients. A retrospective analysis was conducted between June 2013 and September 2017of 88 adult patients with thoracic spinal tuberculosis. All patients were treated with single posterior debridement, bone grafting and instrumentation. The clinical manifestations and laboratory and imageological results were subsequently analysed. All patients were followed for 40.6 ± 4.1 months (range, 36–48 m). Bony fusion was achieved in all bone grafts of thoracic vertebrae. The visual analogue scale scores, erythrocyte sedimentation rate and C-reactive protein levels 6 weeks after surgery and at the final follow up were significantly lower than the preoperative levels (P < 0.05). The postoperative and final follow up kyphosis angles were both significantly smaller than the preoperative kyphosis angles (P < 0.05). The postoperative angle correction rate reached 81.5% and the postoperative angle loss reached only 4.1%. At the last follow up, American Spinal Injury Association improvement was significant, compared with the preoperative levels (P < 0.05). The single posterior approach can achieve satisfactory clinical outcomes in the treatment of thoracic spinal tuberculosis.